Penelitian dan Pengembangan E-Module Geometri Berdasarkan Fase Pembelajaran Geometri - Vina Muthmainna Rianto; Punaji Setyosari; Sulton Sulton (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
The concept of learning geometry is based on phases of learning geometry, by Van Hiele, which enhances about students’ levels of geometric thinking. Drafting geometry e-module based on phases of learning geometry becomes one of the teaching materials and has a role in online and offline learning. This study focuses on developing a geometry e-module, on quadrilaterals. The development model used ADDIE by Branch. The research is participated by 18 students of grade VII in secondary school on Malang. The product has been validated by experts, which were perfectly valid. Meanwhile, the effect of the e-module is determined by looking at the gain score, was 0.3, which indicates that geometry e-module is quite effective in enhancing learning outcomes of quadrilaterals and implemented in classroom or distance learning.